We are entering a new era of problems: AI-generated images in research manuscripts - Kabir Suman Dash; Vini Mehta; Priyanka Kharat (Oral Oncology Reports)
This editorial highlights the significant threat of image fraud that may arise from the use of artificial intelligence (AI) generative technology in academic articles, which has been overlooked. This article examines the impacts of AI algorithms used in instances of academic fraud. This perspective's problem is pertinent not just to computer scientists. As individuals inside the scientific community, we actively participate in the peer-review process. Every individual has the potential to be misled by the AI image-fraud techniques outlined in this article. While algorithm creation is a part of computer science, its influence extends to several scientific disciplines, including biology, medicine, and natural science, as discussed in this review. Creating awareness about this problem is an essential prerequisite for combating it. In addition to state-of-the-art AI research, this article also explores various preventative strategies to address this potential danger.